Phytohormone production and colonization of canola (Brassica napus L.) roots by Pseudomonas fluorescens 6-8 under gnotobiotic conditions - Pallai, Rajash; Hynes, Russell K; Verma, Brij; Nelson, Louise M (Canadian journal of microbiology, 2012)
Pseudomonas fluorescens 6-8, a rhizosphere isolate previously shown to enhance root elongation of canola (Brassica napus L.), was characterized for its ability to produce indole-3-acetic acid and cytokinins in pure culture and in the rhizosphere of canola under gnotobiotic conditions in comparison with the cytokinin-producing strain P. fluorescens G20-18 and its mutant CNT2. Strain 6-8 produced isopentenyl adenosine, zeatin riboside, and dihydroxyzeatin riboside at levels similar to those of G20-18, but only very low concentrations of indole-3-acetic acid. In a gnotobiotic assay canola inoculated with 6-8 and G20-18 had higher concentrations of isopentenyl adenosine and zeatin riboside in the rhizosphere and greater root length than the noninoculated control. The ability of strain 6-8 to colonize canola roots was assessed following transformation with the green fluorescent protein and inoculation onto canola seed in a gnotobiotic assay. Higher populations of strain 6-8 were observed on the proximal region of the root closest to the seed than on the mid and distal portions 9 days after seed inoculation. The ability of P. fluorescens 6-8 to produce cytokinins, colonize the roots of canola seedlings, and enhance root elongation may contribute to its ability to survive in the rhizosphere and may benefit seedling growth.